N-(3-Chlorophenyl)benzamide - Hartmut Fuess; B. P. Sowmya; Jozef Kožíšek; Miroslav Tokarčík; B. Thimme Gowda (Acta Crystallographica Section E, 2008)
The conformation of the N—H bond in the structure of the title compound (N3CPBA), C13H10ClNO, is anti to the meta chloro substituent in the aniline benzene ring, similar to that observed with respect to the ortho chloro substituent in N-(2-chlorophenyl)benzamide (N2CPBA) and meta chloro substituent in N-(3,4-dichlorophenyl)benzamide (N34DCPBA), but in contrast to the syn conformation observed with respect to both the ortho and the meta chloro substituents in N-(2,3-dichlorophenyl)benzamide (N23DCPBA). The bond parameters in N3CPBA are similar to those in N-phenylbenzamide, N2CPBA, N23DCPBA, N34DCPBA and other benzanilides. The amide group –NHCO– makes a dihedral angle of 18.2 (2)° with the benzoyl ring, while the dihedral angle between the two benzene rings is 61.0 (1)°. The molecules are linked into chains along the b axis by N—H...O hydrogen bonds.